The Effect of Foot Massage Relaxation Techniques To Reduce Pain Level In Patients With Ventilator In ICU Cengkareng Hospital In 2022 - Helena Lasria Parhusip; Maria Astrid; Wilhelmus Hary Susilo (Pelopor Publikasi Akademika, 2023)
Pain usualy experienced by patients on ventilator in the ICU. Efforts to reduce pain with foot massage done independently on the patient. Foot massage safe complementary therapy, providing relaxing effect, feeling comfortable and reducing pain. This study used quasi experiment research design with pre and post test control group design. The total sample of 40 respondents was divided into an intervention group 30 respondents were given foot massage once a day for 2 consecutive days, the control group was 10 respondents given analgesic therapy for 2 consecutive days. Post test pain scores 30 minutes after getting treatment on first and second days. Results showed that majority of the age group 46-55 years 30%, majority male 57%, 65% were suctioned, and body position changes 82%, there was difference in pre-test (p = 0.001) and post-test (p=0.007) the intervention group, there was difference in the level of pain after foot massage in the intervention group and the administration of analgesics the control group (p=0.000), there was effect of suctioning mucus (p=0.003), there was effect of changes in body position (p=0.008). This means that foot massage has effect reducing pain levels in patients. This study recommends the need for further research and foot massage one of independent nurse interventions in nursing care for patients with ventilatory pain.